Photobiomodulation by Led Does Not Alter Muscle Recovery Indicators and Presents Similar Outcomes to Cold-Water Immersion and Active Recovery - Malta, Elvis de Souza; Lira, Fabio Santos de; Machado, Fabiana Andrade; Zago, Anderson Saranz; Amaral, Sandra Lia do; Zagatto, Alessandro Moura (Frontiers in Physiology, 2019)
Purpose: The aim of the present study was to investigate the effectiveness of photobiomodulation therapy (PBMT) on muscle recovery based on inflammation (interleukin-10 [IL-10]; tumor necrosis factor-α [TNFα]), muscle damage markers (creatine kinase [CK]; lactate dehydrogenase [LDH]), delay onset muscle soreness (DOMS), and countermovement jump performance (CMJ) after two sprint interval training (SIT) sessions compared with a placebo condition (part-I), as well as to compare the effectiveness of PBMT with active recovery (AR) and cold-water immersion (CWI) (part-II). Methods: Part-I was conducted as a double-blind, randomized and placebo-controlled study and part-II as a parallel-group study. Thirty-six men participated in the studies (12 participants in part-I and 36 participants in part-II). Volunteers performed two SITs interspaced by 24-h (SIT1 and SIT2) to mimic the effect of accumulating 2 consecutive days of SIT. In part-I, only after SIT2, PBMT [Total energy: 600J (300J per leg in 5 spots); wavelength: 660–850 nm] or placebo interventions were performed, while in part-II PBMT (part-I data), AR (15-min; 50% of the maximal aerobic power), or CWI (10-min; 10°C) were carried out, also after SIT2. Blood samples were collected before (i.e., baseline), and 0.5, 1, 24, 48, and 72-h after SIT2, while CMJ and DOMS were measured before, 24, 48, and 72-h after SIT2. Results: In part-I, there were no interactions between PBMT and placebo conditions for any blood markers (P ≥ 0.313), DOMS (P = 0.052), and CMJ (P = 0.295). However, an effect of time was found with increases in LDH, CK, and IL-10 (P ≤ 0.043) as well as a decrease in DOMS at 72-h compared with 24-h (P = 0.012). In part-II, there were no interactions between the PBMT, AR, and CWI groups for any markers at the same moments (P ≥ 0.189) and for the peak and integral values (P ≥ 0.193), for DOMS (P = 0.314) and CMJ (P = 0.264). However, an effect of time was found with an increase in CK and IL-10 (P = 0.003), while DOMS decreased at 48 and 72-h compared with 24-h (P = 0.001). Conclusion: In summary, PBMT had no effect on inflammation, muscle damage, CMJ performance, or DOMS after two consecutive sprint interval training sessions compared to placebo, CWI, and AR strategies.